2015
DOI: 10.1111/1471-0528.13625
|View full text |Cite|
|
Sign up to set email alerts
|

Interpregnancy interval and perinatal outcomes across Latin America from 1990 to 2009: a large multi‐country study

Abstract: ObjectiveTo determine the relationship of interpregnancy interval with maternal and offspring outcomes.DesignRetrospective study with data from the Perinatal Information System database of the Latin American Centre for Perinatology and Human Development, Uruguay.SettingLatin America, 1990–2009.PopulationA cohort of 894 476 women delivering singleton infants.MethodsDuring 1990–2009 the Perinatal Information System database of the Latin American Centre for Perinatology identified 894 476 women with defined inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 21 publications
5
52
2
2
Order By: Relevance
“…The preexisting medical conditions rate in this study (28.8%) was higher than Timofeev's result (0.1‐10.3%) . This might be because we have included a large number of possible co‐morbidities, whereas other studies included only pregestational diabetes and chronic hypertension …”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The preexisting medical conditions rate in this study (28.8%) was higher than Timofeev's result (0.1‐10.3%) . This might be because we have included a large number of possible co‐morbidities, whereas other studies included only pregestational diabetes and chronic hypertension …”
Section: Discussioncontrasting
confidence: 62%
“…However, studies have shown that usage rates for these substances among Chinese women are very low . Data were also not available on the details of the first pregnancy, type of contraception used, or in vitro fertilization . Also, data were collected from three provincial hospitals, thus results may not be generalizable to China as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014; Mignini et al. 2016). A recent study using historical data even showed that as the overall level of child mortality declined, the negative effect of preceding inter‐birth interval length on mortality approached zero (Molitoris 2017).…”
mentioning
confidence: 99%
“…In the following article, there were errors in the abstract and results section on pages 730 and 732 respectively.…”
mentioning
confidence: 99%